Bridging Global Expertise and Classroom Pedagogy: International Partnership and Teacher Professional Transformation - Utari Akhir Gusti; Asep Ihsanudin; Ade Luthfi Munawar; Haryo Mojopahit; Muhammad Shirli Gumilang (Pedagogia: Jurnal Ilmiah Pendidikan, 2026)
This study aimed to assess the impact of the British Council’s partnership through the Nusantara Grow Program on teachers’ professional transformation in schools. The study was motivated by the growing need for sustainable professional development programs that enhance teachers’ pedagogical competencies and readiness to respond to evolving educational demands. An explanatory sequential mixed-methods design was employed, combining quantitative and qualitative data to provide a comprehensive evaluation of the program’s outcomes. Data were collected using the Customer Satisfaction Index (CSI), semi-structured interviews, and classroom observations, focusing on indicators of teacher professionalism. The findings indicate that the Nusantara Grow Program made a significant contribution to improving teachers’ professional competencies, particularly in identifying students’ learning needs, enhancing learning motivation, and strengthening the implementation of formative and summative assessments. Teachers also reported increased confidence, stronger reflective practices, and greater ability to integrate information technology and international learning platforms into classroom instruction. Furthermore, the program expanded teachers’ professional networks by facilitating collaboration with international experts through the British Council’s Massive Open Online Courses (MOOCs), encouraging the adoption of more adaptive, innovative, and globally informed teaching practices. These findings demonstrate that international partnership programs can play an important role in fostering teachers’ professional transformation and supporting continuous professional development in schools.